Nilai Moral Sosial dalam Podcast Kumpulan Puisi Siswa Kelas XI MIPA 1 SMAN 53 Jakarta Timur - Wisesa, Maharani Wahyu; Widiati, Nita (Hiski Malang, 2021)
This study aims to describe the social moral values contained in a collection of podcast poetry for students of class XI MIPA 1 SMAN 53 East Jakarta. The approach used in this research is descriptive qualitative research. This study aims to describe the social moral values contained in a collection of podcast poetry for students of class XI MIPA 1 SMAN 53 East Jakarta. Based on the results of the analysis of 30 poems contained in the poetry collection podcast as a whole, in this study it can be concluded that the moral values contained in the poetry collection podcast for students of class XI MIPA 1 SMAN 53 East Jakarta there are 17 data on the moral values of human relations with God and 54 data on the moral value of human relations with society. Based on the discussion above, it can be concluded that podcast media can be an alternative media during a pandemic to study literary works, especially poetry.